2015
DOI: 10.1111/1552-6909.12739
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Body Mass Index in Overweight Adult Women with Polycystic Ovary Syndrome During a Lifestyle Modification Program

Abstract: Objective To evaluate changes in body mass index (BMI) and health‐related quality of life (HRQoL), including an acne parameter, of overweight adult women with polycystic ovary syndrome (PCOS) during a lifestyle modification program. Design Prospective longitudinal within‐patient study. Setting Department of Reproductive Medicine of the Ghent University Hospital (Belgium). Participants Thirty‐three overweight (BMI ≥ 25 kg/m²) women with PCOS between age 18 and 43 years. Methods Participants followed a 24‐week l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
2
16
2
1
Order By: Relevance
“…Weight issues continued to be an area of concern for adolescent girls in the majority of studies included, 14,[29][30][31][32][33] which has previously been reported in similar studies in adult women. 36,37 Weight was also a driving influence in QoL scores in the study by Trent et al, 24 the largest study to date of QoL in adolescent girls with PCOS and healthy adolescents, in which the majority of adolescent girls with PCOS were overweight or obese (76%). Likewise, two studies only assessed QoL in obese adolescent girls and these were intervention studies that demonstrated improvement in QoL along with some improvement in weight.…”
Section: Discussionmentioning
confidence: 97%
“…Weight issues continued to be an area of concern for adolescent girls in the majority of studies included, 14,[29][30][31][32][33] which has previously been reported in similar studies in adult women. 36,37 Weight was also a driving influence in QoL scores in the study by Trent et al, 24 the largest study to date of QoL in adolescent girls with PCOS and healthy adolescents, in which the majority of adolescent girls with PCOS were overweight or obese (76%). Likewise, two studies only assessed QoL in obese adolescent girls and these were intervention studies that demonstrated improvement in QoL along with some improvement in weight.…”
Section: Discussionmentioning
confidence: 97%
“…People seeking treatment for obesity have lower HRQOL than the general population with obesity and therefore stand to gain the most from weight loss treatment, limiting the generalizability of results from treatment‐seeking populations . In these populations, it may also be exposure to the intervention itself, which causes improved HRQOL independent of actual weight loss .…”
Section: Discussionmentioning
confidence: 99%
“…At the study level, we decided to include only longitudinal observational studies, which are more prone to various types of bias. Our research question could not be answered with randomized control trials, as weight loss interventions do not provide information on weight gain and exposure to interventions themselves may cause HRQOL changes independent of weight loss . In the included studies, long follow‐up times often led to considerable loss to follow‐up and the selection of healthier populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, já foi demonstrado que o treinamento físico aeróbio melhora a função endotelial (BELARDINELLI et al, 2005;DOW et al, 2017). Dessa forma, a melhora de mais escores da função sexual no grupo intermitente, possivelmente ocorreu por uma somatória de fatores, como a redução da RCQ, redução da testosterona, melhora dos escores de ansiedade e depressão e de qualidade de vida, bem como outros fatores não avaliados por este estudo, como VO2máx, o aumento da circulação local e de alteração de fatores metabólicos (ANDERS e HAMPSON, 2005;BELARDINELLI et al, 2005;PALOMBA et al, 2008;TJONNA, A. E. et al, 2008;SIJIE et al, 2012;THOMSON et al, 2012;DE FRÈNE et al, 2015;MATSUO et al, 2015;DOW et al, 2017;GORDON et al, 2017). Esses são fatores bem investigados e avaliados após protocolos de treinamento físico aeróbio, diferente de estudos envolvendo a função sexual.…”
Section: Tabela 8 -Comparação Intergrupos (Gc Gac E Gai) Dos Escoresunclassified